Effectiveness of Acceptance and Commitment-Based Couple Therapy on Communication Patterns and Marital Infidelity in Married Individuals - Khaneghahi, Sofia; Poorjanebollahi Firoozabadi, Mansoure; Koroghli, Mitra; Karimi, Masoomeh (Applied Family Therapy Journal (AFTJ), 2024)
Objective: This study aimed to investigate the effectiveness of Acceptance and Commitment-Based Couple Therapy (ACT) on communication patterns and marital infidelity among married individuals in Yazd.Methods: The research method was quasi-experimental. The population consisted of all married individuals attending psychological counseling and service centers in Meybod. Using questionnaires on communication patterns and marital infidelity, and employing purposive sampling, 20 couples with higher scores were selected from a pool of 50 couples. They were randomly assigned to either the experimental group (10 couples) or the control group (10 couples). The experimental group underwent Acceptance and Commitment Therapy, while the control group received no treatment. Post-tests were administered to both groups. Results, analyzed using covariance analysis.Findings: Findings showed that Acceptance and Commitment-Based Couple Therapy significantly impacts the communication patterns of married individuals. Additionally, it significantly affects marital infidelity among married individuals.Conclusion: Thus, ACT can be used to enhance couple’s relationship and prevent infidelity and divorce.